Effects of increasing dried distiller’s grains on feed intake - C W Hastad; N Z Frantz; Jim L Nelssen; Robert D Goodband; Michael D Tokach; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
Recent studies have shown that dried distiller's grains with solubles (DDGS) has an ME value similar to that of corn, but pigs fed diets with DDGS have a lesser feed intake than do those fed corn. We conducted three studies to evaluate the effects of DDGS on palatability and feed intake of growing pigs. In Exp. 1, 90 gilts (initially 58.2 lb) were used to evaluate the effects of a diet based on cornsoybean meal, alone or with 30% DDGS from two different sources, on feed preference. Source 1 DDGS was obtained from an ethanol plant built before 1990 and source 2 was obtained from a plant built after 1990. Each pen of pigs had two feeders, one with the cornsoybean meal diet and the other with one of the DDGS sources. There were 10 pens with six pigs per pen and 10 pens with 3 pigs per pen, for a total of 90 gilts; all pigs were blocked by weight. The location of the feeders was moved morning and evening each day. From d 0 to 7, there were no differences in ADFI among the dietary treatments. From d 7 to 13 and overall (d 0 to 13), however, feed intake was less (P0.33) on feed intake in either the cornsoybean meal or DDGS diets. These studies demonstrate that pigs prefer corn-soybean diets to diets containing DDGS. For these experiments, the source of DDGS or the addition of a feed flavor did not change palatability. Although it seems that the ME content of DDGS could be comparable to that of corn, palatability problems may affect pig performance, even when DDGS included at low rates in the diet.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Swine; Pigs; Feed intake; DDGS